Implementation of imla’ online learning in the LPBA Al Qodiri Islamic Boarding School Jember - Kamilin, Bahrudin Rosyid; Anam, Syamsul; Maulana, Asep; Alfan, Muhammad (Abjadia : International Journal of Education, 2025)
Facing the era of globalization and technological developments lately, the world is faced with a fast flow of information. Therefore, the important of information technology and the internet in various fields of life, including the world of education. This study aims to describe the implementation of Imla online learning. This research uses descriptive qualitative research. The object of this research is the student the students of LPBA Al Qodiri Islamic boarding School Jember. This research technique uses observation and interviews. The results showed that the implementation of Imla online learning could improve students’ ability to write Arabic. Judging from the learning that has been applied with the progress of each meeting, where students can write correctly or not make mistakes. Judging from the results of the research that there has been an increase in students, let online-based learning continue to be carried out, because with the online learning of Imla ‘this makes people who want to learn very easy to obtain, then it will also have a positive impact on smartphone users who is on the rise at this time.